Financial Crises and Political Radicalization: How Failing Banks Paved Hitler's Path to Power - DOERR, SEBASTIAN; GISSLER, STEFAN; PEYDRÓ, JOSÉ‐LUIS; VOTH, HANS‐JOACHIM (Journal of Finance, 2022)
ABSTRACT Do financial crises radicalize voters? We study Germany's 1931 banking crisis, collecting new data on bank branches and firm‐bank connections. Exploiting cross‐sectional variation in precrisis exposure to the bank at the center of the crisis, we show that Nazi votes surged in locations more affected by its failure. Radicalization in response to the shock was exacerbated in cities with a history of anti‐Semitism. After the Nazis seized power, both pogroms and deportations were more frequent in places affected by the banking crisis. Our results suggest an important synergy between financial distress and cultural predispositions, with far‐reaching consequences.